Dividend Payments in Listed Companies Partly Owned by Private Pension Funds (OFE) - Uchman, Jacek (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The aim of the paper was to estimate the frequency of dividend payment made by companies partly owned by private pension funds (OFE). In other words, it concentrates on the effect for dividend payment resulting from the fact that OFE are shareholders of companies that is the most important group of institutional investors on Polish stock market. The basic research question is: do companies with OFE shares pay dividends more often than the average stock companies. The number of companies paying dividends was analysed. The empirical research was based on the data coming from the companies from stock market indexes. The results are not obvious, however, they show that the companies partly held by OFE paid dividends more often than all companies from the analysed indexes. OFE are the point of interest in the paper as long as they refer to the distribution of profits of companies.